Inventing English : a portable history of the language - Lerer, Seth, 1955- (Columbia University Press, 2007)
Presents a history of the English language, beginning with the Old English of the seventh century, through the Great Vowel Shift between the time of Chaucer and Shakespeare, and the later full emergence of modern English.